Characterizing Trends in the Use of Food Donations and Other Food-Related Community-Based Social Assistance Programs in a Cohort of New Food Bank Users in Quebec, Canada - Elsury Johanna Pérez; Elsury Johanna Pérez; Elsury Johanna Pérez; Mabel Carabali; Mabel Carabali; Geneviève Mercille; Geneviève Mercille; Geneviève Mercille; Marie-Pierre Sylvestre; Marie-Pierre Sylvestre; Marie-Pierre Sylvestre; Federico Roncarolo; et al. (Frontiers Media S.A., 2024)
Objective: To characterize 12-month trends in the use of food donations and other food-related community-based social assistance programs (CB-SAPs) during the first year following the enrollment of new food bank (FB) users in Quebec, Canada.Methods: A cohort of 1,001 newly registered FB-users in Quebec from the Pathways Study were followed-up during 12-month following baseline assessment. Outcomes were monthly use of food donations and other food-related CB-SAPs. Main predictors were alternative food source utilization (AFSU) profiles: 1) exclusive-FB-users; 2) FB+fruit/vegetable-market-users; and 3) Multiple/diverse-AFS-users. Covariates included sociodemographic characteristics, health status, and major life events. We fit Bayesian hierarchical mixed-effect models, accounting for spatial clustering, temporal correlation, and censoring.Results: We observed an overall downward trend of food donation use among study completers (n = 745). Each AFSU profile had a distinctive monthly trend of food donation use, but probabilities of use across the three profiles overlapped, between 44% and 55%. The use of other food-related CB-SAPs was low and not correlated with AFSU profiles.Conclusion:De novo FB-users use food donations in different ways over time according to specific contextual AFSU profiles.